Exploration of used cooking oil through art activities against children in Seri Iskandar / Hairulnisak Merman, Gladys Tagie and Wan Nurhasyimah W. Mohd Apandi - Merman, Hairulnisak; Tagie, Gladys; W. Mohd Apandi, Wan Nurhasyimah (2022)
Removing used cooking oil into drains and public places has a detrimental effect on the environment, such as clogged drains, polluted rivers, and soil being damaged by the loss of mineral resources. Clogged drains cause pest inbreeding, while contaminated water sources have an effect on the destruction of aquatic life. This issue is one of the primary sources of pollution in the Seri Iskandar area. This study was conducted to explore and identify the potential of used cooking oil through art activities for the Seri Iskandar community, especially children. This study used a qualitative methodology as its primary research approach. Researchers gather information through primary data collection methods such as interviews, observations, and fieldwork. Secondary methods are derived from data sources such as books, journals, and magazines. The findings revealed that used cooking oil can not only be recycled and used to make candles and biodiesels, but it can also be used as an ingredient in the creation of creative artworks. This art activity also helps children learn the fundamentals of art skills such as mixing materials, shaping, and carving. Children are also taught the value of environmental stewardship through the adoption of a sustainable lifestyle. As a result, this study has the potential to increase the public's knowledge and awareness of the potential of used cooking oil to be used as a creative artwork. Furthermore, this study has significant implications for the local community's awareness of the development of environmental sustainability to ensure a better quality of life in the future.